Comparative education as a field in Asia: retrospect and prospect. Issue 3 (3rd July 2017) - Manzon, Maria
Abstract: Comparative education in Asia is witnessing changing discourses, structural opportunities, and invigorated leadership. This article will review the institutionalization of comparative education in Asia from a sociological perspective, drawing on Bourdieu's theory on the logic of social practice. After giving an overview of the historical roots of Asian comparative education, I will describe broadly its landscape noting developments in the last two decades since 1995, the foundational year of the Comparative Education Society of Asia (CESA). Four main themes are explored: comparative education teaching, professional societies, research centres, and specialist publications. With a baseline understanding of the infrastructures of the field in Asia and the power dynamics that shape them, I will propose an agenda for Asian comparative education to offer meaningful contributions to multipolar knowledge production in the field. Priority themes and directions will be highlighted to articulate a stronger Asian voice and leadership in an increasingly diverse and uncertain world.